An antifreezing and thermally stable hydrogel electrolyte for high-performance all-in-one flexible supercapacitor. (June 2022) - Hu, Qinzheng; Cui, Shuzhen; Sun, Kanjun; Shi, Xiuting; Zhang, Mingxin; Peng, Hui; Ma, Guofu
Highlights: A novel wide temperature tolerant hydrogel (EG-PAM/MMT-EMIMBF4 ) is designed. Supercapacitor is prepared by polymerization of pyrrole on both sides of hydrogel. Supercapacitor exhibits excellent tensile, twisting and compression properties. Supercapacitor shows good electrochemical properties and wide temperature tolerance. Abstract: Hydrogel electrolyte have multifunctional properties in the flexible supercapacitors, which can have excellent mechanical behavior and wide temperature tolerance. However, the hydrogel electrolytes with poor mechanical properties, unsatisfactory ionic conductivity and narrow temperature range are still a huge challenge to limit their widely use in the flexible supercapacitors. Herein, a novel ethylene glycol-containing polyacrylamide/montmorillonite/ionic liquid (EG-PAM/MMT/EMIMBF4, EG-PME) hydrogel with significant stretchability, high ionic conductivity and wide temperature tolerant was synthesized by a cross-linking polymerization process. The double-network structure can improve the mechanical properties of hydrogel. Moreover, the introduction of EG and EMIMBF4 into the hydrogel can improve the temperature range. Furthermore, an integrated flexible supercapacitor with wide temperature range was fabricated by in-situ polymerization polypyrrole electrodes onto hydrogel. The integrated flexible supercapacitors have superior toughness under different mechanical deformation (e.g., stretch, compression and twisting ). The EG-PME-PPy composite film possesses high single electrode areal capacitance of 212 mF cm −2 at 0.8 mA cm −2, high energy density of 9.4 μWh cm −2 at power density of 319.5 μW cm −2, and good ionic conductivity of 5.18 mS cm −1 at -30 °C, as well as high ionic conductivity of 33.3 mS cm −1 at 40 °C. The integrated flexible supercapacitors have the satisfying electrochemical properties due to the rapid ion diffusivity and low charge transfer resistance of the integrated all-in-one hydrogel. Therefore, the developed all-in-one flexible supercapacitor based on multifunctional hydrogel can be a next-generation promising power sources. Graphical abstract: Image, graphical abstract